PENDEKATAN PROBLEM-BASED LEARNING DALAM PEMBELAJARAN PRAKTIK KERJA LAPANGAN TERAPI FISIK - Wara Kushartanti (Jurnal Cakrawala Pendidikan, 2010)
Abstract: The Problem-Based Learning Approach in Physical Therapy FieldWorks. The objectives of the study are to identify strategic application of Problem-Based Learning (PBL) in physical therapy field works and to improve studentsmastery in physical therapy in terms of cognitive, affective, and psychomotordomains. This action research study consisted of three cycles, each of whichincluded four stages, namely planning, implementing the plan, monitoringactivities and progress, and reflection. The participants were 23 seventh semesterstudents taking physical therapy field works in 2007. In the first cycle, studentstheoretical mastery was inadequate. In the second cycle they did more extensiveliterature search to expand theories. In the third cycle they learned more aboutempirical cases, not just theories, so that they better skills in implementing thewhole PBL activities and managed to attain the course objectives. PBL is thereforesuitable for advanced students prior to their professional development.Keywords: problem based-learning, physical therapy field works